Caenorhabditis elegans as a complete model organism for biosafety assessments of nanoparticles. (April 2019) - Wu, Tianshu; Xu, Hongsheng; Liang, Xue; Tang, Meng
Abstract: The number of biosafety evaluation studies of nanoparticles (NPs) using different biological models is increasing with the rapid development of nanotechnology. Thus far, nematode Caenorhabditis elegans ( C. elegans ), as a complete model organism, has become an important in vivo alternative assay system to assess the risk of NPs, especially at the environmental level. According to results of qualitative and quantitative analyses, it can be concluded that studies of nanoscientific research using C. elegans is persistently growing. However, the comprehensive conclusion and analysis of toxic effects of NPs in C. elegans are limited and chaotic. This review focused on the effects, especially sublethal ones, induced by NPs in C. elegans, including the development, intestinal function, immune response, neuronal function, and reproduction, as well as the underlying mechanisms of NPs causing these effects, including oxidative stress and alterations of several signaling pathways. Furthermore, we presented some factors that influence the toxic effects of NPs in C. elegans . The advantages and limitations of using nematodes in the nanotoxicology study were also discussed. Finally, we predicted that the application of C. elegans to assess long-term impacts of metal oxide NPs in the ecosystem would become a vital part of the nanoscientific research field, which provided an insight for further study. Graphical abstract: Image 1 Highlights: The publication related to the nanoscientific research using C. elegans is increasing in recent years. The toxicity of NPs can be assessed in C. elegans through endpoints of biological functions and molecular markers. Factors of both NPs physicochemical properties and C. elegans cultivation environment can influence the toxicity of NPs. There are several advantages and drawbacks of C. elegans in nanotoxicology studies.